2017
DOI: 10.1128/jvi.01854-16
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Bovine Papillomavirus E2 Protein on Tyrosine Regulates Its Transcription and Replication Functions

Abstract: Papillomaviruses are small, double-stranded DNA viruses that encode the E2 protein, which controls transcription, replication, and genome maintenance in infected cells. Posttranslational modifications (PTMs) affecting E2 function and stability have been demonstrated for multiple types of papillomaviruses. Here we describe the first phosphorylation event involving a conserved tyrosine (Y) in the bovine papillomavirus 1 (BPV-1) E2 protein at amino acid 102. While its phosphodeficient phenylalanine (F) mutant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 61 publications
3
23
1
Order By: Relevance
“…The papillomavirus E2 protein is posttranslationally modified by the host cell to coordinate viral replication and transcription with the epithelial growth and differentiation program. We previously reported that phosphorylation of Y102 impaired viral replication and transcription in bovine papillomavirus (BBPV) E2 (7). Our subsequent publication revealed that FGFR3 induced phosphorylation of E2 and inhibited viral DNA replication; however, this outcome also occurred with Y102F, inferring that this tyrosine is not the target of this kinase (12).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The papillomavirus E2 protein is posttranslationally modified by the host cell to coordinate viral replication and transcription with the epithelial growth and differentiation program. We previously reported that phosphorylation of Y102 impaired viral replication and transcription in bovine papillomavirus (BBPV) E2 (7). Our subsequent publication revealed that FGFR3 induced phosphorylation of E2 and inhibited viral DNA replication; however, this outcome also occurred with Y102F, inferring that this tyrosine is not the target of this kinase (12).…”
Section: Discussionmentioning
confidence: 96%
“…The first tyrosine (Y) phosphorylation was identified at position 102 in the TAD of the bovine papillomavirus (BPV) E2 protein (7). By comparing wild-type (WT) E2 to phosphodeficient and phosphomimetic mutants, we demonstrated that this phosphorylation restricted E1-dependent replication, as well as transcriptional activation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…E2 also binds to the viral helicase E1, which initiates replication of the PV episome. Posttranslational modifications have been found to regulate the functions of the E2 protein (7)(8)(9)(10). Our lab recently discovered and characterized a novel tyrosine phosphorylation site at position 102 (Y102) within the TAD of bovine papillomavirus type 1 (BPV-1) E2 (8).…”
Section: Importancementioning
confidence: 99%
“…The E2 proteins of different PV types have been shown to be modified by phosphorylation, acetylation, and sumoylation (15)(16)(17)(18)(19)(20)(21)(22). S298 and S301, which are located in the hinge region, are the major phosphorylation sites of bovine papillomavirus 1 (BPV1) E2 (19).…”
mentioning
confidence: 99%